2019
DOI: 10.1103/physreva.99.053816
|View full text |Cite
|
Sign up to set email alerts
|

Efficient representation of Gaussian states for multimode non-Gaussian quantum state engineering via subtraction of arbitrary number of photons

Abstract: We introduce a complete description of a multi-mode bosonic quantum state in the coherent-state basis (which in this work is denoted as "K" function ), which-up to a phase-is the square root of the well-known Husimi "Q" representation. We express the K function of any N -mode Gaussian state as a function of its covariance matrix and displacement vector, and also that of a general continuous-variable cluster state in terms of the modal squeezing and graph topology of the cluster. This formalism lets us characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…The technology of Gaussian operations and measurements is nowadays relatively well established and easily implementable, but this limited set of transformations is insufficient for many quantum information protocols. For example, by exploiting pure Gaussian transformation, quantum computation cannot show a quantum advantage [21], entanglement cannot be distilled [22], quantum error correction against Gaussian noise cannot be realized [23,24], and the capacity of optical communication cannot be reached [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The technology of Gaussian operations and measurements is nowadays relatively well established and easily implementable, but this limited set of transformations is insufficient for many quantum information protocols. For example, by exploiting pure Gaussian transformation, quantum computation cannot show a quantum advantage [21], entanglement cannot be distilled [22], quantum error correction against Gaussian noise cannot be realized [23,24], and the capacity of optical communication cannot be reached [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the NOON state is a useful entangled resource, which has been generated [6] and applied to improve phase sensitivity in quantum metrology [7]. A large number of theoretical and experimental studies have demonstrated that entanglement between Gaussian entangled states can be increased via Gaussian or non-Gaussian operations [8][9][10][11][12][13][14][15][16][17][18][19][20]; these operations can be divided into local [21][22][23][24] and nonlocal [25,26]. Many nonlocal operations have the effect of delocalization, which can entangle the input separable states or change the entanglement of the input entangled states.…”
Section: Introductionmentioning
confidence: 99%
“…But producing such states-and non-Gaussian CV states more generallyis an extremely challenging endeavor, with proof-ofprinciple GKP realizations so far limited to non-photonic platforms [19,20]. The discovery and analysis of Gaussian boson sampling (GBS) [21,22], however, has provided a valuable framework for preparing non-Gaussian optical states [23][24][25][26]. Also straddling the interface between CV and DV-in that it leverages both CV fields and single-photon detection-GBS circuits can in principle produce arbitrary non-Gaussian states through ancilla modes and postselection on particular detection patterns, analogous to the probabilistic gates of linear-optical quantum computation (LOQC) in the DV paradigm [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Also straddling the interface between CV and DV-in that it leverages both CV fields and single-photon detection-GBS circuits can in principle produce arbitrary non-Gaussian states through ancilla modes and postselection on particular detection patterns, analogous to the probabilistic gates of linear-optical quantum computation (LOQC) in the DV paradigm [1,2]. The design [18,[26][27][28] and implementation [29][30][31] of GBS-type circuits for non-Gaussian state preparation have so far focused on the path degree of freedom (DoF), a natural choice given its long history in optics and well-known unitary decomposition procedure [32,33]. But other DoFs offer promise as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation